Synthesis of ester- and phosphonate-functionalized auI-imidazolylidene chlorides through the isonitrile route - Wurm, Thomas; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2017)
Starting from DMSAuCl, isonitriles and functionalized propargylammonium salts in the presence of simple trimethylamine as auxiliary base, unsymmetrically substituted ester- and phosphonate-functionalized AuI-imidazolylidene complexes were synthesized in an easy-to-use modular one-pot template synthesis. In the course of the reaction, after the initial nucleophilic addition of the amine to the gold(I)-activated isonitrile, a Michael addition closes the N-heterocyclic carbene (NHC) ring. Then the remaining double bond migrates into the NHC ring, evidently a more stable position than the initial exocyclic double bond. These functional groups attached to the back bone of the NHC ligands represent ideal handles for a further modification of the system, for example an attachment to larger assemblies or heterogenization by an attachment to surfaces are conceivable.
Gesehen am 29.08.2017